The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/2358-2936e2018028
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of European and African species of genus Diaptomus (Copepoda: Calanoida: Diaptomidae): a track analysis

Abstract: The distributional patterns of 13 species of Diaptomus Westwood, 1836 were analyzed using the panbiogeographical method of track analysis. Locality records were compiled from the literature and mapped for the construction of individual tracks for each species. These tracks were superimposed to find the generalized tracks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Diaptomus castor Jurine, 1820 reported for Ile Rousse (Corsica) by Richard (1894Richard ( -1895 is here ascribed to a misidentification of D. cyaneus since D. castor does not occur in the Mediterranean area (Kiefer, 1978), and the record was published before the description of D. cyaneus (Gurney, 1909). Other references: Champeau, 1971;Champeau and Thiéry, 1990;Marrone and Naselli-Flores, 2004;Marrone 2006;Marrone et al 2006bMarrone et al , 2009Marrone et al , 2013Marrone et al , 2017Alfonso and Belmonte, 2013;Troia et al, 2016;Belmonte, 2018;dos Santos-Silva et al, 2018. Diaptomus (Chaetodiaptomus) serbicus Gjorgjewič, 1907. TYR, APU, SIC.…”
Section: Annotated Checklistmentioning
confidence: 96%
See 1 more Smart Citation
“…Diaptomus castor Jurine, 1820 reported for Ile Rousse (Corsica) by Richard (1894Richard ( -1895 is here ascribed to a misidentification of D. cyaneus since D. castor does not occur in the Mediterranean area (Kiefer, 1978), and the record was published before the description of D. cyaneus (Gurney, 1909). Other references: Champeau, 1971;Champeau and Thiéry, 1990;Marrone and Naselli-Flores, 2004;Marrone 2006;Marrone et al 2006bMarrone et al , 2009Marrone et al , 2013Marrone et al , 2017Alfonso and Belmonte, 2013;Troia et al, 2016;Belmonte, 2018;dos Santos-Silva et al, 2018. Diaptomus (Chaetodiaptomus) serbicus Gjorgjewič, 1907. TYR, APU, SIC.…”
Section: Annotated Checklistmentioning
confidence: 96%
“…In the study area, the species is so far only reported for temporary ponds in Latium (e.g., Stoch 2006a), Sicily (Marrone et al, 2006a), and Apulia (Alfonso and Belmonte, 2011). Other references: Vagaggini et al, 2002;Marrone, 2006;Marrone et al, 2006bMarrone et al, , 2009Marrone et al, , 2010Marrone et al, , 2013Marrone et al, , 2017Marrone et al, , 2019Seminara et al, 2015Seminara et al, , 2016Belmonte, 2018;dos Santos-Silva et al, 2018. Eudiaptomus gracilis (Sars, 1863.…”
Section: Annotated Checklistmentioning
confidence: 99%